Simulation of Turbulent Emulsification in a Sonolator Mixer: Interpretation of Drop Breakage Time. Issue 8 (29th April 2019) - Bagkeris, Ioannis; Michael, Vipin; Prosser, Robert; Kowalski, Adam J.
Abstract: The simulation of dilute emulsions in a model ACIP2 Sonolator is investigated using computational fluid dynamics and population balance methods. Two breakage frequency models are used that differ in the expression of the drop breakage time. Drop breakage modeling based on homogenous isotropic turbulence (HIT) shows poor agreement of the Sauter mean diameter when compared to the experiments; simulations with the empirical model from Alopaeus et al. yield better agreement. By perturbing the classical HIT spectrum, it is shown that the breakage time in the empirical model corresponds to a non‐isotropic energy spectrum. Such spectra have been observed in the non‐isotropic near field in a model A Sonolator, which provides a plausible explanation of why the empirical model performs better than the HIT‐based model. Abstract : A unified framework for interpreting the time scale term of droplet breakage kernels based on the underlying turbulence structure is considered. Time scale terms that correspond to non‐isotropic turbulence conditions typically encountered in high‐shear mixers are able to better capture the droplet breakup in such devices and yield closer agreement with experiments.